Market-based or policy strategies to increase the cultivation of legumes for livestock? Effects on the cropping pattern and economic performance - Efstratios Michalis; Athanasios Ragkos; Chrysovalantis Malesios (Agricultural and Food Economics)
Abstract Legume crops, the production of which is related to their use in animal nutrition (referred to in this study as “legumes for livestock—LL” and include species such as bean, lupin, pea, vetch and clover), have positive effects on the economic performance of farms and environmental outcomes, although their relation to sustainable weed management practices (SWMP) has received limited attention. The expansion of LL in Europe is limited due to market constraints, despite important policy incentives. This study was designed to investigate whether a policy-oriented Scenario (S1) or a market-based Scenario (S2) could induce the expansion of the cultivation of LL as well as to examine the possible impact on the economic performance of farming systems, including cost savings related to pest management. A farm typology was developed according to the level of expenses of farms for crop protection and their implemented SWMP. Using technical and economic data from 45 farms that cultivate annual arable crops in Greece, with special emphasis on LL, a Linear Programming model was constructed to examine the potential role of each one of the three identified farm types in the expansion of LL in Central Greece (Baseline Solution—BS). Following the BS, the effects of the two Scenarios were examined through a Price Parametric Programming approach. The solutions revealed that the valorization of LL had a significant economic potential for all farm types. In addition, it was found that a substantial policy incentive of increasing the coupled payments of LL by 128% (S1) can have an equivalent impact on the expansion of LL as modest levels of market interventions—through the achievement of higher yields or/and higher selling prices—to increase the revenues of LL by 59% (S2). Farms that relied more on chemical pesticides could play a more decisive role in expanding LL. The novel aspect is related to the investigation of the economic performance of different farm types cultivating LL with a specific focus on potentially higher profitability related to SWMP. Furthermore, this study contributed to the “policy versus market solutions” debate toward the expansion of LL.